2018
DOI: 10.1371/journal.pone.0199442
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal expression of Slug and Snail in human oral cancer cells

Abstract: Snail, also called Snai1, is a key regulator of EMT. Snail plays crucial roles in cancer progression, including resistance to anti-tumor drugs and invasion by various cancer cells. Slug, also known as Snai2, is also involved in the aggravation of certain tumors. In this study, we examined the roles of Slug in human oral squamous cell carcinoma (OSCC) cells. Slug is highly expressed in these cells, and Slug siRNA effectively represses anti-tumor drug resistance and invasive properties. In addition, transforming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 42 publications
1
48
0
1
Order By: Relevance
“…miR-200 family members have been shown to inhibit SLUG in esophageal cancer and prostate cancer [Liu et al, 2013;Zong et al, 2019;Basu et al, 2020], while SLUG can inhibit miR-200 in prostate cancer [Liu et al, 2013]. On the other hand, SLUG and SNAIL have been reported to inhibit each other in oral cancer [Nakamura et al, 2018] and breast cancer [Ganesan et al, 2015]. The effect of SLUG on EMP dynamics can also be influenced by upstream regulators of SLUG such as RNF8, YAP, C/EBPδ, miR-151, CBP, RCP, HDAC1, HDAC3, BRD4 and STAT3 [Cheng et al, 2020;Chesnelong et al, 2019;Kuang et al, 2020;Wang et al, 2020;Daugaard et al, 2017;Jury et al, 2020;Dai et al, 2020;Hwang et al, 2017;Hu et al, 2020;Shafran et al, 2020].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-200 family members have been shown to inhibit SLUG in esophageal cancer and prostate cancer [Liu et al, 2013;Zong et al, 2019;Basu et al, 2020], while SLUG can inhibit miR-200 in prostate cancer [Liu et al, 2013]. On the other hand, SLUG and SNAIL have been reported to inhibit each other in oral cancer [Nakamura et al, 2018] and breast cancer [Ganesan et al, 2015]. The effect of SLUG on EMP dynamics can also be influenced by upstream regulators of SLUG such as RNF8, YAP, C/EBPδ, miR-151, CBP, RCP, HDAC1, HDAC3, BRD4 and STAT3 [Cheng et al, 2020;Chesnelong et al, 2019;Kuang et al, 2020;Wang et al, 2020;Daugaard et al, 2017;Jury et al, 2020;Dai et al, 2020;Hwang et al, 2017;Hu et al, 2020;Shafran et al, 2020].…”
Section: Discussionmentioning
confidence: 99%
“…Previous mathematical models developed for EMP signaling have often not distinguished between SNAIL and SLUG, and taken them as a single node [Tian et al, 2013;Hong et al, 2015;Mooney et al, 2016;Lu et al, 2013]. With increasing knowledge about the different roles of SNAIL and SLUG in influencing EMP in different contexts, including their effect on one another [Ganesan et al, 2015;Varankar et al, 2019;Nakamura et al, 2018;Gras et al, 2014;Sundararajan et al, 2019;Hamidi et al, 2020;Swain et al, 2019;Chen, and Gridley, 2013], it becomes imperative to investigate their differential roles from a detailed mechanistic perspective. Therefore, we have adopted a mechanism-based computational systems biology approach to elucidate these differences.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies in a variety of tissue types have also found EMT-TFs, namely SNAIL1/2, ZEB1/2 and TWIST, to directly confer drug-resistance in cancer [70][71][72][73][74][75][76][77][78][79][80][81] , as summarised in Table 2. Upregulation of these transcription factors alone can be sufficient to confer drug resistance [71,75] .…”
Section: Drug Resistance: Where Does Emt Come Into Play?mentioning
confidence: 99%
“…Head and neck squamous cell carcinoma (HNSCC), originating from the mucosa of the oral cavity, nasopharyngeal cavity, and pharyngeal cavity, is the most‐common malignancy with high morbidity and mortality in the head and neck region . Despite the rapid progress that has been made in the prevention, diagnosis and treatment of HNSCC, the 5‐year survival rate remains poor due to rapid cervical lymph node metastasis, local recurrence, and a high incidence of drug resistance . However, it is difficult to accurately predict the outcomes of HNSCC patients due to the lack of robust valuable biomarkers are lacking.…”
Section: Introductionmentioning
confidence: 99%